2019
DOI: 10.1089/jpm.2019.0210
|View full text |Cite
|
Sign up to set email alerts
|

Early Integrated Telehealth versus In-Person Palliative Care for Patients with Advanced Lung Cancer: A Study Protocol

Abstract: Introduction: Early palliative care (PC) integrated with oncology care improves quality of life (QOL), depression symptoms, illness understanding, and end-of-life (EOL) care for patients with advanced lung cancer. The aims of this trial are to compare the effect of delivering early integrated PC through telehealth versus in-person on patient and caregiver outcomes. We hypothesize that both modalities for delivering early PC would be equivalent for improving patient QOL, communication about EOL care preferences… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 31 publications
(16 citation statements)
references
References 35 publications
0
16
0
Order By: Relevance
“…Five ongoing studies were found in the literature search and details are summarized in the Supplementary Material (Table S2 ) [ 39 , 40 , 41 , 42 , 43 ].…”
Section: Resultsmentioning
confidence: 99%
“…Five ongoing studies were found in the literature search and details are summarized in the Supplementary Material (Table S2 ) [ 39 , 40 , 41 , 42 , 43 ].…”
Section: Resultsmentioning
confidence: 99%
“…Despite these limitations, this model of care has been received positively by both patients and palliative care providers [ 70 ]. Research on several telehealth palliative care interventions is ongoing [ 71 , 72 ], and the next decade will undoubtedly bring a wealth of evidence in this regard.…”
Section: Settings For Specialized Palliative Carementioning
confidence: 99%
“…Since 2018, we have been collecting data on PC clinician-reported challenges for in-person and video visits as part of an ongoing multisite randomized control trial of early integrated PC for patients with advanced lung cancer. 24 Here, we conducted a post hoc analysis of this data to describe trends in PC clinician-reported challenges for in-person and video visits before and during the COVID-19 pandemic across multiple U.S. cancer centers.…”
Section: Introductionmentioning
confidence: 99%